2015
DOI: 10.1016/j.eimc.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the etiology, incidence and prognosis of acute lower respiratory track infections in human immunodeficiency virus patients

Abstract: a b s t r a c tAim: To describe the, incidence, the changes in the etiology and the prognosis of lower respiratory tract infection (LRTI) in HIV infected patients, presenting by the first time to the Emergency Department (ED), during years 2000-2010. Study design: Prospective collection of data. Metbods: Data were collected on the first visit of HIV-infected patients at our ED due to a LRTI, (defined according to the criteria of the European Respiratory Society), between 1/1/2000 and 31/12/2010. A series of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…28 Stemming from different methodologies, there is disagreement in the association between lower CD4 cell counts and worse outcomes, including multilobar consolidation, longer time to clinical stability and increased mortality. Some studies have reported no impact of this marker on CAP outcome, 11,17 whereas others have conversely found a significant impact on mortality, prompting authors to recommend admission of all patients in the <200 cells/mL subgroup. 13,15,29 Taking into account our results, in addition to CURB-65 scores, low CD4 cell counts seem to be independent predictive factors in the severity assessment of HIV-positive patients presenting with CAP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 Stemming from different methodologies, there is disagreement in the association between lower CD4 cell counts and worse outcomes, including multilobar consolidation, longer time to clinical stability and increased mortality. Some studies have reported no impact of this marker on CAP outcome, 11,17 whereas others have conversely found a significant impact on mortality, prompting authors to recommend admission of all patients in the <200 cells/mL subgroup. 13,15,29 Taking into account our results, in addition to CURB-65 scores, low CD4 cell counts seem to be independent predictive factors in the severity assessment of HIV-positive patients presenting with CAP.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 HIV infection has been consistently described as a major risk factor for CAP, [5][6][7][8] which is considered a stage 3 disease in the World Health Organization HIV staging classification 9 and an AIDS-defining illness by the American Centers for Disease Control and Prevention (CDC) when recurrent. 10 Despite a reported decline in incidence over the last two decades, [7][8]11 this condition remains frequent in this population, with its relative burden presently greater than before. [11][12][13][14] In fact, CAP among HIVinfected patients has been found in some studies performed in high-income settings to be the most prevalent severe non-AIDS-defining infection and one of the most frequent reasons for hospital admission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5) Although the incidence of RI has decreased, and its etiology has changed due to the introduction of cART, it has a non-negligible mortality and often requires admission to an intensive care unit (ICU). (6) The study objectives were to clarify, in a cohort of HIV-infected patients, if the usual clinical manifestations of AICMV have changed, and if RI has an important role in the presentation of AICMA, Furthermore, we wanted to find out which microorganisms cause it, and what the 30-day mortality is.…”
Section: Introductionmentioning
confidence: 99%